2008
DOI: 10.1111/j.1752-7325.2007.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in the Acceptance of Medicaid Patients in Dental Practices

Abstract: Objectives: Medicaid enrollees disproportionately experience dental disease and difficulties accessing needed dental care. However

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 14 publications
(17 reference statements)
1
31
0
Order By: Relevance
“…The small number of participating dentists contributes to racial or ethnic disparities in number of visits within Medicaid. 18,19 Racial or ethnic differences between dentists and patients within the California population, as indicated by disproportionately fewer Latino (11 percent) and African American (1 percent) dentists, may be another reason. 20 Difficulties in making or keeping appointments may also limit the ability of some groups to gain access to dental care.…”
Section: Discussionmentioning
confidence: 97%
“…The small number of participating dentists contributes to racial or ethnic disparities in number of visits within Medicaid. 18,19 Racial or ethnic differences between dentists and patients within the California population, as indicated by disproportionately fewer Latino (11 percent) and African American (1 percent) dentists, may be another reason. 20 Difficulties in making or keeping appointments may also limit the ability of some groups to gain access to dental care.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is consistent with previous reports (e.g., dental specialty and race of the dentist). 7,23 …”
Section: Discussionmentioning
confidence: 99%
“…Okunseri and colleagues found that characteristics of dental providers were predictive of participation in dental Medicaid. 23 In a report on dental practices and Medicaid in the state of Wisconsin, minority dentists were twice as likely as White dentists to accept Medicaid patients. Logan and colleagues found that Blacks and Hispanic dentists were more likely to be Medicaid participants in Florida than other dentists.…”
mentioning
confidence: 99%
“…8 In addition, there is a severe shortage of minority dentists to serve the growing racial/ethnic minority Medicaid enrollees. As Okunseri and colleagues 9 have reported, minority dentists are more likely to accept new Medicaid patients. Furthermore, studies have documented that children from low-income families have lower odds of receiving comprehensive dental care and higher odds of having acute dental disease than children from middle-income and upper-income families.…”
Section: Introductionmentioning
confidence: 88%